Community-Based Waste Management in Cisauk District, Tangerang Regency (Case Study of Melati Bersih Waste Bank, Griya Serpong Asri Housing) - Ziyad HIzbullah Sutoni; Hasuri Waseh (International Journal of Social Sciences Review, 2026)
Community Base Solid Waste Management one element that enables a community can develop themselves and achieve progress. This study aims to describe the process of community empowerment in the waste management system through the principle of 3R waste banks that are in Clean Jasmine Waste Bank. Type of research is descriptive qualitative. Data col-lected by observation, interviews (interview), and documentation. Testing and analysis of data is done by triangulation of data and classifying data is systematically then outlines the existing data in the field that describes the form of community empowerment in the Wast bank. The results showed that community base solid waste management in Clean Jasmine Waste Bank was not yet optimal.Community Response, People are not consistent in depositing their waste every month , People have not been able to implement a system for sorting waste from their homes, People prefer to sell their waste to collectors. Keywords: Community Base Solid Waste Mangement, Waste Bank, 3R